Crucial materials? How export restrictions upstream boost manufacturing exports downstream - Eva Wichmann (FIW - Research Centre International Economics, 2017)
This paper shows both theoretically and empirically how raw material rich countries use export restrictions upstream to give manufacturing sectors downstream a competitive advantage. For young and relatively small industries this can be seen as a type of infant industry protection that takes advantage of the global value chain. Estimating a fixed effect model, I provide evidence that export restrictions on industrial raw materials upstream help promote manufacturing exports downstream.
Keywords: F12; F14; L25; L61; L71; Q3; 330; Export Restrictions; International Trade; Competitive Advantage; Resource Rich; Manufacturing; Metals; Minerals